Real-time head acceleration measurement in girls` youth soccer - Hanlon, E. M.; Bir, C. A. (Medicine & Science in Sports & Exercise, 2012)
Purpose: The purpose of the current study was to collect real-time head acceleration data for soccer impacts during girls` youth (U14) soccer play.